Stopping Hot Money or Signaling Bad Policy? Capital Controls and the Onset of Currency Crises. - Reuven Glick; Michael Hutchison (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
Restrictions on international capital transactions and other payments are usually designed to limit volatile short-term capital flows (hot money) and stabilize the exchange rate. Their imposition, however, may have the opposite effect by inadvertently signaling the continuation of macroeconomic imbalances and inconsistent (bad) future policy (Bartolini and Drazen, 1997a,b). This paper investigates these alternative hypotheses by testing the impact of restrictions on international capital flows and other payments controls on the likelihood of currency crises. We employ a comprehensive sample of 90 developing and emerging-market economies over the 1975-1997 period, identifying 160 currency crises. Restrictions on international capital flows, current accounts, and international payments are associated with a higher probability of the onset of a speculative attack on the currency. This finding is robust to alternative measures of liberalization on international payments and the exchange rate regime, controlling for macroeconomic determinants of currency instability, and taking into account instability emanating from the banking sector. There may be some individual exceptions but the weight of the evidence suggests that countries imposing capital restrictions are sending a bad signal to markets, in turn increasing the likelihood of a net capital outflow and a currency crisis.
Keywords: 330